Recurrent osteolytic lesions and subcutaneous fat necrosis in association with a developmental pancreatic cyst. Issue 10 (October 1979) - Hollingworth, P; Isaacs, D; Bydder, G
Abstract : A girl had repeated episodes of widespread osteolysis, subcutaneous fat necrosis, and periarticular fat necrosis mimicking arthritis. Her symptoms persisted for 4 years, after in initial episode of severe abdominal pain, and were accompanied by only minor abdominal symptoms. She was found to have a developmental pancreatic cyst (which was excised).